Redox-responsive supramolecular amphiphiles based on a pillar[5]arene for enhanced photodynamic therapy. Issue 19 (21st April 2016) - Chen, Ye; Rui, Leilei; Liu, Lichao; Zhang, Weian
Abstract : Supramolecular amphiphiles based on a pillar[5]arene with enhanced photodynamic therapy have been fabricated. Abstract : Supramolecular amphiphiles based on a pillar[5]arene with enhanced photodynamic therapy have been fabricated. Supramolecular amphiphiles based on host–guest complexation between a poly(ethylene glycol)-functionalized pillar[5]arene (PEG-P[5]A) and a pyridinium-terminated porphyrin derivative bearing a disulfide bond (TPPC6-SS-Py) could self-assemble into spherical micelles in aqueous solution with good colloidal stability as confirmed by transmission electron microscopy (TEM) and dynamic light scattering (DLS). Also, PEG-P[5]A/TPPC6-SS-Py micelles exhibited rapid release of porphyrin photosensitizers in a reducing environment. In addition, these micelles demonstrated nearly no toxicity in the dark but a higher photocytotoxicity upon light irradiation evaluated by the MTT assay. Flow cytometry and confocal laser scanning microscopy (CLSM) revealed a more effective cellular uptake property compared with free porphyrin. Therefore, novel reduction-responsive supramolecular amphiphiles with rapid drug release and superior cell internalization ability are constructed, which may provide a platform for drug delivery systems.